2005
DOI: 10.1002/art.21298
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose prednisolone in addition to the initial disease‐modifying antirheumatic drug in patients with early active rheumatoid arthritis reduces joint destruction and increases the remission rate: A two‐year randomized trial

Abstract: Objective. To assess the efficacy of low-dose prednisolone on joint damage and disease activity in patients with early rheumatoid arthritis (RA).Methods. At the start of their initial treatment with a disease-modifying antirheumatic drug (DMARD), patients with early (duration <1 year) active RA were randomly assigned to receive either 7.5 mg/day prednisolone or no prednisolone for 2 years. Radiographs of the hands and feet were obtained at baseline and after 1 and 2 years and scored according to the Sharp scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
184
1
16

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(225 citation statements)
references
References 38 publications
21
184
1
16
Order By: Relevance
“…We next used a categorical approach based on the notion that achieving low disease activity and remission are ultimate goals of RA therapy (34)(35)(36)(37)(38)(39)(40)(41). We therefore categorized the disease activity status of the patients at 1 year as follows: remission (SDAI Յ3.3), low disease activity (SDAI 3.3 to Յ11), moderate disease activity (SDAI Ͼ11 to Յ26), or high disease activity (SDAI Ͼ26).…”
Section: Methodsmentioning
confidence: 99%
“…We next used a categorical approach based on the notion that achieving low disease activity and remission are ultimate goals of RA therapy (34)(35)(36)(37)(38)(39)(40)(41). We therefore categorized the disease activity status of the patients at 1 year as follows: remission (SDAI Յ3.3), low disease activity (SDAI 3.3 to Յ11), moderate disease activity (SDAI Ͼ11 to Յ26), or high disease activity (SDAI Ͼ26).…”
Section: Methodsmentioning
confidence: 99%
“…Our approach to the use of prednisone is supported by evidence that the disease-modifying and erosion-inhibiting benefits of low-dose oral prednisone therapy (5-10 mg/d) are sustained for at least 2 years, with minimal corticosteroid-related adverse effects. 70,71 Because most of the benefit is in the first year, our recommendation is to continue prednisone at 5 mg/d for 6 months to 1 full year before gradually tapering in decrements of 1 mg every 2 to 4 weeks. It is likely that treatment using low-dose prednisone may increase the probability of a successful outcome of MTX therapy.…”
Section: Treatment Approach Initial Treatment Approachmentioning
confidence: 99%
“…Clinical studies have demonstrated that treatment of early RA patients with a combination of a tumor necrosis (TNF) inhibitor and methotrexate results in better clinical outcomes. 29,30 The Behandel Strategieen (BeSt) study was a single-blind clinical trial where RA patients with less than 2 years of disease duration were randomized to 1 [anti-CCP]). Physicians often use the 1987 American College of Rheumatology (ACR) Classification Criteria of RA to assist in making the diagnosis.…”
Section: Benefits Of Aggressive Treatment In Early Ramentioning
confidence: 99%